From explicit prohibition to ambiguity in prohibiting - Chamizo-Domínguez, Pedro José (My University, 2015)
This contribution will deal with two topics closely related and intermingled. I firstly will try to show how one of the salient features of euphemisms is their ambiguity and/or vagueness (Grondelaers and Geeraerts, 1998) to the extent that even sentences in which lexicalised euphemisms are used can become dysphemistic if they are not ambiguous. This means that ambiguous and/or vague sentences play a fundamental, cognitive role (Tuggy, 2006). This is the case of a well-known excerpt from Somerset Maugham in which, in spite of the fact that all the nouns used are euphemisms, the excerpt itself can be considered dysphemistic. Conversely, I will show two instances from two songs in which female pudenda are euphemistically and ambiguously alluded to. Secondly, I will try to apply my previous reflections to politically correct language. In order to do so I will take as a starting point the fact that political correctness spread across the western countries in the same decade (1960-1970) in which the motto “Il est interdit d’interdire” got also trendy (Hughes, 2006 and 2010). As a result of the fact that the noun ‘prohibition’ (and its cognates, derivatives and synonyms) became “prohibited” as a politically incorrect word, prohibition itself has to be phrased in ambiguous sentences. For instance, instead of the (currently) politically incorrect notice “No Smoking” or “Smoking is prohibited”, we frequently find the politically correct one “Thank you for not smoking”, where the sentence meaning is pretty different from what the author of the notice tries to mean; since the sentence meaning is that someone thanks you for not smoking, while what the author of the notice intends to mean that smoking is prohibited.
El trabajo fue presentado en la sección monográfica sobre lenguaje tabú en el mencionado congreso.
Keywords: Ambigüedad; Lenguaje; Euphemism; Dysphemism; Ambiguity vaganess; political correctness, euphemism, dysphemism, ambiguity vaganess,